The comparative effectiveness of statin therapy in selected chronic diseases compared with the remaining population - Sheng Xia; Murphy Michael J; MacDonald Thomas M; Wei Li (BMC, 2012)
Abstract Background Total cholesterol (TC) concentration is the most commonly used measure of statin efficacy in the UK. This study aimed to evaluate the effectiveness of statins in lowering TC, cardiovascular events (CV) and mortality five common chronic diseases (chronic obstructive pulmonary disease (COPD), osteoarthritis (OA), rheumatoid arthritis (RA), chronic kidney disease (CKD), and diabetes mellitus (DM)) and to compare effectiveness with the rest of the population not recorded as having these diseases. Methods A population-based cohort study was conducted in Tayside population who had at least two TC measurements between 1993 and 2007. There were 12,140 patients with chronic diseases and 9,481 patients in the rest of the population not recorded as having these chronic diseases. The main outcomes were TC change from baseline, CV events and all-cause mortality. Results Statin-associated TC reductions varied from 15% to 28% with baseline value of between 5.1 and 5.9 mmol/L in the primary prevention (PP) and from 7% to 23% with baseline value of 4.5 to 5.2 mmol/L in the secondary prevention (SP) among chronic diseases patients. In the rest of the population, TC reductions with statins were 31% in PP and 28% in SP with baselines of 6.3 mmol/L and 5.3 mmol/L, respectively (test of heterogeneity with chronic disease groups: p < 0.001). A notional reduction of 0.5 mmol/L in TC predicted variable reductions in incident CV events of 30% in RA, 19% in CKD, and 20% in DM, and recurrent CV events by 62% in COPD, 16% in CKD, and 19% in DM. The corresponding figures for the rest of population were 12% for incident CV events and 17% for the recurrent CV events, respectively. Risk reductions for all-cause mortality varied from 20% to 36% in PP and from 18% to 40% in SP, except in OA or RA patients in the chronic diseases and 11% in PP and 16% in the rest of population (test of heterogeneity: p > 0.05). Conclusions The effectiveness of statins in common chronic diseases varied. With the exception of diabetes, statins tends to be less effective in patients with the chronic diseases compared with the rest of the study population. Changes in TC with statins appear not to correlate well with the changes in cardiovascular events and all-cause mortality.